Current trends in the selection of young swimmers - Feroyan, Eduard (Національний технічний університет "Харківський політехнічний інститут", 2024)
The purpose of the study: to determine the indicators by which it is possible to assess the prospects of a child in swimming, who is able to achieve high sports results in the future. As a result of the study, it was found that the indicators characterizing the predisposition of children 7-8 years old to master swimming skills are: duration of breath holding during inhalation and exhalation; accuracy of reproduction of the water surface using water-supporting movements. Four types of mental reactions of 7–8-year-old children to contact with the aquatic environment have been identified: positive, conditionally positive, conditionally negative, negative. New biological aspects of selection can help specialists more accurately select new swimmers, as well as timely determine and predict their prospects.
Keywords: young swimmers; swimming skills; mental reactions; children